2008
DOI: 10.1093/treephys/28.11.1675
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and modeling the variation in species-specific transpiration in temperate deciduous hardwoods

Abstract: We investigated which parameters required by the MAESTRA model were most important in predicting leaf-area-based transpiration in 5-year-old trees of five deciduous hardwood species-yoshino cherry (Prunus x yedoensis Matsum.), red maple (Acer rubrum L. 'Autumn Flame'), trident maple (Acer buergeranum Miq.), Japanese flowering cherry (Prunus serrulata Lindl. 'Kwanzan') and London plane-tree (Platanus x acerifolia (Ait.) Willd.). Transpiration estimated from sap flow measured by the heat balance method in branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 32 publications
4
36
0
1
Order By: Relevance
“…We measured 11 field-and container-grown tree species (Acer buergeranum Miq., Acer rubrum L., Betula nigra, Gleditsia triacanthos, Fraxinus pennsylvanica, Paulownia elongata, Paulownia fortunei, Prunus serrulata Lindl. 'Kwanzan', Prunus × yedoensis Matsum., Quercus nuttallii, Quercus phellos) (33,34) and one Freeman Acer rubrum cultivar (Autumn Blaze) over five growing seasons under nonresource limiting nursery conditions (34). Measured leaves were from continuously flushing, fully exposed, upper branches of 2.5-to 12-yold saplings; leaf age was therefore similar across the growing season.…”
Section: Methodsmentioning
confidence: 99%
“…We measured 11 field-and container-grown tree species (Acer buergeranum Miq., Acer rubrum L., Betula nigra, Gleditsia triacanthos, Fraxinus pennsylvanica, Paulownia elongata, Paulownia fortunei, Prunus serrulata Lindl. 'Kwanzan', Prunus × yedoensis Matsum., Quercus nuttallii, Quercus phellos) (33,34) and one Freeman Acer rubrum cultivar (Autumn Blaze) over five growing seasons under nonresource limiting nursery conditions (34). Measured leaves were from continuously flushing, fully exposed, upper branches of 2.5-to 12-yold saplings; leaf age was therefore similar across the growing season.…”
Section: Methodsmentioning
confidence: 99%
“…While g 0 has commonly been assumed to be close to zero with little effect on water fluxes (Caird et al 2007;Zeppel et al 2010), recent studies have shown that g 0 could be higher than previously expected in many ecosystems (Ogle et al 2012) and that its value could change seasonally (Barnard and Bauerle 2013). In a recent study using MAESTRA, it was shown that g 0 had a large effect on TR (Bowden and Bauerle 2008). Stomatal conductance is driven by g 0 or g 1 depending on the assimilation ( (A) Sensitivity of the metamodel to parameters using the Sobol index, (B) time series of daily simulated tree transpiration and sap flow measurements from 1.5 to 2.5 years after planting, and (C) mean percentage error, with standard deviation, between simulated and measured tree TR depending on the time scale.…”
Section: Parameters Set Constant Across the Standmentioning
confidence: 98%
“…Previous sensitivity analyses of the tree-scale MAESTRA model generally investigated local sensitivity and did not take the natural variability of the parameters into account (Bowden and Bauerle 2008) or were limited to a small number of physiological parameters (e.g., Bauerle and Bowden 2011). Some recent studies have shown the limitations of such local approaches in which the sensitivities of carbon and water fluxes to physiological parameters were strongly influenced by atmospheric CO 2 concentration or meteorological conditions such as light or temperature (Bauerle et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has also been recognised that transpiration often varies amongst species (Oren and Pataki, 2001;Ewers et al, 2002;Bowden and Bauerle, 2008) and up-scaling to forest transpiration in species-rich indigenous forests is complex.…”
Section: A D Clulow Et Al: Extending Periodic Eddy Covariance Latementioning
confidence: 99%